PENINGKATAN KEMAMPUAN MAHASISWA DALAM MERANCANG PEMBEJALARAN PADA MATA KULIAH MAGANG 2 MELALUI TEKNIK BELAJAR BERPASANGAN - Larasati . (Sasindo : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2014)
This study aims to determine the increase in the ability of students in designing learning Indonesian through learning techniques in pairs and determine behavioral changes after being given treatment . This research is research PTK ( Classroom Action Research ) consisting of two cycles , namely cycle 1 and cycle 2 with design each cycle through planning procedures , action ( implementation ) , observation , and reflection . Pnelitian results showed an increase in pre-cycle , the first cycle to the second cycle . In phase prasiklus , upon ability to design students learning at 59.3 . After being given the action on the first cycle value increased by an average of 70.05 , and rose again in the second cycle of 84.65 . This paired learning activities has a positive effect on student attitudes .Keywords : learning , apprentice 2 , a technique learned in pairs